Parenting Behaviors after Moderate – Severe Traumatic Injury in Early Childhood - Narad, Megan E. (Dev Neurorehabil, 2018)
PURPOSE: Examine the impact of traumatic brain injury (TBI) on parenting behavior over time. METHOD: Included 206 children (3–7 years old) with moderate-severe TBI or orthopedic injury, using a prospective longitudinal cohort study design. Assessments completed at baseline, 6-months, 12-months, 18-months, 3.5 years, and 6.8 years after injury. Dependent variables included authoritative, permissive, and authoritarian parenting. RESULTS: Injury characteristics had limited impact on parenting behaviors over time. Levels of authoritative parenting remained stable over time; however, levels of warmth and involvement declined over time for those with TBI. Levels of permissive and authoritarian parenting declined for all participants by 3.5 years post injury. SES and stressors impacted parenting behaviors. CONCLUSIONS: While there was limited effect of TBI on parenting behavior over time, it remains unclear how individuals respond to these parenting behaviors years after injury. Clinicians should monitor family and parenting behaviors to foster an environment to promote positive recovery.